1990
DOI: 10.1007/bf01135443
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Visually Evoked Potential topography associated with a visual vigilance task

Abstract: This paper describes data which demonstrate a correlation between the magnitude of the Steady-State Visually Evoked Potential (SSVEP) and visual vigilance. The SSVEP was recorded from 64 scalp sites and elicited by a 13Hz uniform visual flicker presented continuously while subjects undertook a visual vigilance task. Fifteen right-handed males were required to view three times a series of 180 geometrical shapes comprising a sequence of 60 squares, 60 circles and a further 60 squares. Each viewing of the 180 sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 23 publications
7
99
1
Order By: Relevance
“…One technique is the GFP (Lehmann and Skrandies 1980;Vecchiato et al, 2010Vecchiato et al, , 2011 and the other is the Steady State Topography (Silberstein et al, 1990). The GFP can monitor alpha desynchronization and theta increases in the same timeframe as a video; tracking cortical brain changes with events being observed by a participant.…”
Section: Page 46 Of 54 European Journal Of Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…One technique is the GFP (Lehmann and Skrandies 1980;Vecchiato et al, 2010Vecchiato et al, , 2011 and the other is the Steady State Topography (Silberstein et al, 1990). The GFP can monitor alpha desynchronization and theta increases in the same timeframe as a video; tracking cortical brain changes with events being observed by a participant.…”
Section: Page 46 Of 54 European Journal Of Marketingmentioning
confidence: 99%
“…Elevated levels of attention, working memory, emotion, and imagination during a narrative video would suggest a strong fit between story object and story-receiver. Silberstein et al, 1990) and GFP analysis (Lehmann and Skrandies, 1980;Vecchiato et al, 2010). However, SST is a commercially owned and restricted technique, so in this study GFP was used.…”
Section: Fit Between Story Object and Story-receivermentioning
confidence: 99%
“…Steady-state potentials in the auditory or visual modality have been shown to be sensitive for tonic subjective states, such as anesthesia (Plourde & Picton, 1990), sleep (Picton et al, 1987), or vigilance (Silberstein et al, 1990). In addition, the amplitudes of ssVEPs are modulated as a function of phasic changes in the individual, such as cognitive performance (Silberstein, Ciorciari, & Pipingas, 1995) or visual spatial selective attention (Morgan, Hansen, & Hillyard, 1996).…”
Section: The Research Problemmentioning
confidence: 99%
“…SSVEP has been used more and more in the study of cognitive tasks including memory [2][3][4][5][6], decision selecting [7], emotional processing [8], and of various clinical diseases [9][10][11][12][13]. In these studies, the amplitude and phase changes were thought of as indicators of the modulation of SSVEP by a cognitive task, but none had ever studied the mechanism of this modulation.…”
mentioning
confidence: 99%
“…The ERP is extracted by the traditional average method directly, while the SSVEP is estimated by the technique named steady-state probe topography (SSPT) [7]. By computing the correlation coefficient (CC) between the ERP and SSVEP, it is found that amplitude modulation of SSVEP by ERP does exist and is notable in the frontal and occipital areas, where the neural activities of SSVEP and ERP are both strong.…”
mentioning
confidence: 99%